Functional Electrical Stimulation Therapy for Retraining Reaching and Grasping After Spinal Cord Injury and Stroke - Kapadia, Naaz; Moineau, Bastien; Popovic, Milos R. (Frontiers in Neuroscience, 2020)
Neurological conditions like hemiplegia following stroke or tetraplegia following spinal cord injury, result in a massive compromise in motor function. Each of the two conditions can leave individuals dependent on caregivers for the rest of their lives. Once medically stable, rehabilitation is the main stay of treatment. This article will address rehabilitation of upper extremity function. It is long known that moving the affected limb is crucial to recovery following any kind of injury. Overtime, it has also been established that just moving the affected extremities does not suffice, and that the movements have to involve patient’s participation, be as close to physiologic movements as possible, and should ideally stimulate the entire neuromuscular circuitry involved in producing the desired movement. For over four decades now, functional electrical stimulation (FES) is being used to either replace or retrain function. The FES therapy discussed in this article has been used to retrain upper extremity function for over 15 years. Published data of pilot studies and randomized control trials show beyond doubt that FES therapy produces transformational changes in arm and hand function. There are specific principles of the FES therapy as applied in our studies i.e. stimulation is applied using surface stimulation electrodes, there is minimum to virtually no pain during application, each session lasts no more than 45-60 min, the technology is quite robust and can make up for specificity to a certain extent, and fine motor function like two finger precision grip can be trained (i.e. thumb and index finger tip to tip pinch). The FES therapy protocols can be successfully applied to individuals with paralysis resulting from stroke or spinal cord injury.